Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada Rocket Chicken Bantul - Rui Restu Ade Nugraha; Bangun Putra Prasetya (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to analyze the influence of work discipline and work environment on employee performance at Rocket Chicken Bantul. Work discipline is an important factor that reflects employee discipline in carrying out their duties and responsibilities, while the work environment includes physical and non-physical conditions that affect employee comfort and productivity. The research method used was a survey with a questionnaire distributed to 100 respondents who were Rocket Chicken Bantul employees. The data obtained was analyzed using multiple linear regression to determine the influence of these two variables on employee performance. The research results show that work discipline and work environment have a significant influence on employee performance. Work discipline shows a more dominant influence than the work environment. These findings provide important implications for Rocket Chicken Bantul management to improve employee performance through increasing work discipline and improving the work environment.